Innate and adaptive immune responses toward nanomedicines - Iara Maíra de Oliveira Viana; Sabrina Roussel; Joan Defrêne; Eliana Martins Lima; Frédéric Barabé; Nicolas Bertrand (Elsevier, 2021)
Since the commercialization of the first liposomes used for drug delivery, Doxil/Caelyx® and Myocet®, tremendous progress has been made in understanding interactions between nanomedicines and biological systems. Fundamental work at the interface of engineering and medicine has allowed nanomedicines to deliver therapeutic small molecules and nucleic acids more efficiently. While nanomedicines are used in oncology for immunotherapy or to deliver combinations of cytotoxics, the clinical successes of gene silencing approaches like patisiran lipid complexes (Onpattro®) have paved the way for a variety of therapies beyond cancer. In parallel, the global severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has highlighted the potential of mRNA vaccines to develop immunization strategies at unprecedented speed. To rationally design therapeutic and vaccines, chemists, materials scientists, and drug delivery experts need to better understand how nanotechnologies interact with the immune system. This review presents a comprehensive overview of the innate and adaptative immune systems and emphasizes the intricate mechanisms through which nanomedicines interact with these biological functions.